Evaluating constraints on offshore wind farm installation across the Taiwan Strait by exploring the influence of El Niño-Southern Oscillation on weather window assessment - Wan-Ling Tseng; Cheng-Wei Lin; Yi-Chi Wang; Huang-Hsiung Hsu; Kuan-Ming Chiu; Yueh-Shyuan Wu; Yi-Huan Hsieh; Ying-Ting Chen (Heliyon, 2024)
The transition to renewable energy sources, such as offshore wind farms, is essential in mitigating climate change. Taiwan has set ambitious targets to harness wind energy from the Taiwan Strait, but offshore wind farm installations are highly dependent on weather conditions, particularly wind speeds. This study examines the relationship between the El Niño-Southern Oscillation (ENSO) and offshore wind farm installation by assessing weather windows—periods with wind speeds below 12 m per second at a height of 100 m for at least 12 h. Our analysis shows that during La Niña years, the number of feasible weather windows decreases by up to 40 %, particularly between October and June, compared to neutral and El Niño years. This decrease can be as high as fourfold in December, significantly impacting installation schedules. Seasonal variations are also notable, with wind speeds exceeding 12 m s−1 in winter 66.4 % of the time, compared to 29.4 % in spring, making spring and summer the most favorable periods for installation. However, even during these favorable seasons, La Niña years can bring higher wind speeds, necessitating careful planning. These results underscore the importance of integrating ENSO forecasts into project planning to avoid installation delays and optimize installation timelines. By leveraging seasonal and interannual climate variability predictions, decision-makers can improve the resilience of offshore wind farm projects and ensure efficient energy transition strategies.